A comparison of coronary heart disease risk factor prevalence among offshore and onshore workers in the petroleum industry in Nigeria - Iwot, Isang A. (Stellenbosch : Stellenbosch University, 2016)
Thesis (MFamMed)--Stellenbosch University, 2015.